A Role for Matrix Metalloproteinases in Nicotine-Induced Conditioned Place Preference and Relapse in Adolescent Female Rats. (January 2013) - Natarajan, Reka; Harding, Joseph W.; Wright, John W.
Reconfiguration of extracellular matrix proteins appears to be necessary for the synaptic plasticity that underlies memory consolidation. The primary candidates involved in controlling this process are a family of endopeptidases called matrix metalloproteinases (MMPs); however, the potential role of MMPs in nicotine addiction-related memories has not been adequately tested. Present results indicate transient changes in hippocampal MMP-2, -3, and -9 expression following context dependent learning of nicotine-induced conditioned place preference (CPP). Members of a CPP procedural control group also indicated similar MMP changes, suggesting that memory activation occurred in these animals as well. However, hippocampal MMP-9 expression was differentially elevated in members of the nicotine-induced CPP group on days 4 and 5 of training. Inhibition of MMPs using a broad spectrum MMP inhibitor (FN439) during nicotine-induced CPP training blocked the acquisition of CPP. Elevations in hippocampal and prefrontal cortex MMP-3 expression—but not MMP-2 and -9—accompanied reactivation of a previously learned drug related memory. Decreases in the actin regulatory cytoskeletal protein cortactin were measured in the HIP and PFC during the initial two days of acquisition of CPP; however, no changes were seen following re-exposure to the drug related environment. These results suggest that MMP-9 may be involved in facilitating the intracellular and extracellular events required for the synaptic plasticity underlying the acquisition of nicotine-induced CPP. Furthermore, MMP-3 appears to be important during re-exposure to the drug associated environment. However, rats introduced into the CPP apparatus and given injections of vehicle rather than nicotine during training also revealed a pattern of MMP expression similar to nicotine-induced CPP animals.